Antipyretic effect of the aqueous extract obtained from leaves of Neurolaena lobata (Asteraceae) on a pyretic model induced by brewer's yeast - García González, Mildred (2007)
Neurolaena lobata is a bush native of the tropics, that can be found mainly in the Caribbean and Central American areas. Based on TRAMIL surveys, N. lobata leaves are used for the preparation of many remedies among the indigenous cultures, to treat several illnesses associated with fever. Based on that, the main objective of this study was to determine whether the aqueous extract of N. lobata leaves has antipyretic activity on an experimental animal system. We used Wistar rats (n=40), which were divided into 4 groups, and fever was induced in 3 of the groups with brewer’s yeast. The idea behind the study was to compare the antipyretic effect obtained with acetaminophen and the aqueous extract of N. lobata leaves, and both of them with a control of distilled water (placebo). All three groups receiving brewer’s yeast experienced a pyretic statistically significant effect (p<0.05), while the negative control that did not receive the yeast challenge, showed no effect. Group A received distilled water as a placebo (2 ml/animal), group B received acetaminophen as an antipyretic treatment (1000 mg/kg), group C received the aqueous extract of N. lobata leaves as the experimental solution (2000 mg/kg) and Group D received no treatment (negative control). Group A shown no antipyretic effect, while groups B and C showed an effect of up to 2.9 oC (p<0.05). Treatment with acetaminophen and N. lobata extract showed an antipyretic effect within 30 minutes. In conclusion, we showed that the aqueous extract of N. lobata leaves has an antipyretic effect, therefore the traditional use is validated in rats. This extract could be partially helpful as a remedy to control fever in the absence of other available drugs.